Reproductive health in indigenous Chihuahua: giving birth ‘alone like the goat’. - Chopel, Alison M. (Ethnicity & Health, 2014)
Introduction.Indigenous peoples in the state of Chihuahua, Mexico, are known to outsiders as the Tarahumaras. The Tarahumaras are one of the few cultural groups known to have no traditional birth attendants, and Tarahumara women often give birth alone and outdoors. Currently, little is known about this group, their health status or their culture. Objective.The objective of this study was to assess the state of reproductive health outcomes, risks, protective factors, beliefs and behaviors in the Tarahumara population. Design.This paper reports on the qualitative results of a mixed methods study, comprised of focus groups, interviews, participatory exploratory methods, ethnographic observation and household surveys investigating the reproductive health status of the Tarahumara peoples and contextual factors influencing it. Qualitative data is presented, supported by preliminary quantitative findings. Results.This study supports speculation that the Tarahumara population is burdened by severe maternal health problems. The sample size was too small to definitively assess risk factors for the outcome of maternal mortality, but qualitative findings point to some important contextual issues that contribute to participants' perceptions of susceptibility to and severity of the problem, their reproductive health beliefs and behaviors, and barriers to behavior change. Major issues included disparities in biomedical knowledge, trust between non-indigenous providers and indigenous patients, and structural issues including access to medical facilities and infrastructure. Conclusion.Qualitative data is drawn upon to make recommendations and identify lessons applicable to similar situations where cultural minorities suffer serious health inequities. This study underscores the importance of needs and assets assessment, as it reveals unique contextual factors that must be taken into account in intervention design. Also, collaborative partnership with community members and leaders proved to be invaluable in the research, warranting further collaboration by both governmental and non-governmental groups attempting to improve the health of this population. This becomes especially important when making and enforcing health policy.